Efektivitas Komunikasi Antarpribadi Mahasiswa IAIN Kendari Melalui Media Sosial di Masa Covid 19 - Resky Rahayu; Rahmawati Rahmawati; Yusyrifah Halid; Mansur Mansur (Institut Agama Islam Negeri Kendari, 2022)
This study aims to determine the effectiveness of interpersonal communication between IAIN Kendari students, in this case students of the Ushuluddin Adab and Da'wah Faculty through WhatsApp social media during the Covid-19 pandemic. This study used descriptive qualitative method. In taking the sample, this research used purposive sampling method. Subjects in this study amounted to 21 informants. Data collection techniques used are interview, observation and documentation techniques. The results showed that interpersonal communication made by students through WhatsApp social media was quite effective, even though the communication carried out by informants used WhatsApp social media, but the equality between informants and their communicants made them remain open to each other about their personalities, understand each other and provide mutual positive support between informants and their partners. his communicant. WhatsApp social media has features that are quite supportive for interpersonal communication during the Covid-19 pandemic, such as voice messages, video calls, sharing documents, photos and videos. Barriers that often occur in interpersonal communication through WhatsApp are networks that are sometimes less stable, limited internet quota, differences in language style and communicant responses that cannot be seen directly. Keywords: Effectiveness of Interpersonal Communication, Social Media, WhatsApp, Covid-19.